Germination of Canarium Odontophyllum seeds as affected by desiccation / Aziela Masarip, Fui Ying Tsan and Darius El-Pebrian - Masarip, Aziela; Fui, Ying Tsan; El-Pebrian, Darius (Universiti Teknologi MARA, Sabah, 2020)
Canarium odontophyllum is a rare tropical fruit that is primarily propagated by seeds. However, there is little information regarding its seed handling and germination. As low seed moisture content (MC), generally that below 10%, is the key determinant to successful seed storage while avoiding microbial damage, the objective of this study was, hence, set to investigate C. odontophyllum’s seed germination as affected by desiccation using drying beads (DBs) at room temperature or convection oven at 40C to varying seed MCs, from its initial MC of above 20% down to that below 10%. It was found that the seeds tolerated fast dehydration within 24h at room temperature using DBs. They retained 90% germination despite seed MC was reduced to below 10%. Desiccation tolerance with DBs was, however, found only with seeds extracted from fresh fruits. As the fruits started rotting with wrinkled appearance and fungi on the pericarp from four days after harvest onwards, the seeds extracted from them died at MC of below 15%. A slower seed drying method using convection oven at higher temperature of 40C, on the other hand, took 72h to bring the seed MC down to < 10%.